Strategi Pemasaran Pedagang Pakaian Bekas Pakai Import (Cakar Bongkar) di Pasar Sentral Nabire - Liza Meichy E. Komul; Adrian Mjesfa; Yellia Priciliya Uktolseja; Albert Muyapa; Julius Denny Polii (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
The purpose of this study is to describe the marketing strategies and adaptability of “cakar bongkar” (second-hand clothing) traders in responding to market dynamics in Nabire City. This study employs a qualitative approach, as it is appropriate for addressing research problems that require an in-depth understanding of the socio-economic realities in Kalibobo Market and Karangtumaritis Market in Nabire City. The data used in this study consist of primary data as the main source and secondary data as supporting and relevant information. Data collection methods are carried out using the triangulation principle, namely through direct observation, in-depth interviews, and documentation. Informants are selected using snowball sampling and purposive sampling methods to obtain comprehensive and representative information. Data processing and analysis are conducted through the stages of data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that the informants apply five (5) marketing strategies in selling second-hand clothing (cakar bongkar), namely: (1) sourcing strategies, (2) pricing and promotion strategies, (3) word-of-mouth marketing strategies, (4) strategies for building social relationships with customers, and (5) product display strategies using prototype tables to attract consumer attention.